Different Synthesis Protocols for Co3O4–CeO2 Catalysts—Part 1: Influence on the Morphology on the Nanoscale. Issue 2 (10th November 2014) - Yang, Jingxia; Lukashuk, Liliana; Akbarzadeh, Johanna; Stöger‐Pollach, Michael; Peterlik, Herwig; Föttinger, Karin; Rupprechter, Günther; Schubert, Ulrich
Abstract Co3O4‐modified CeO2 (Co/Ce 1:4) was prepared by a combination of sol–gel processing and solvothermal treatment. The distribution of Co was controlled by means of the synthesis protocol to yield three different morphologies, namely, Co3O4 nanoparticles located on the surface of CeO2 particles, coexistent Co3O4 and CeO2 nanoparticles, or Co oxide structures homogeneously distributed within CeO2. The effect of the different morphologies on the properties of Co3O4–CeO2 was investigated with regard to the crystallite phase(s), particle size, surface area, and catalytic activity for CO oxidation. The material with Co3O4 nanoparticles finely dispersed on the surface of CeO2 particles had the highest catalytic activity.